2008
DOI: 10.1007/s00439-008-0507-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3)

Abstract: Autosomal recessive hypotrichosis (LAH3) is a rare hair disorder characterized by sparse hair on scalp and the rest of the body of affected individuals. Recently mutations in a G protein-coupled receptor gene, P2RY5, located at LAH3 locus, have been reported in several families with autosomal recessive hypotrichosis simplex and woolly hair. For the present study, 22 Pakistani families with autosomal recessive hypotrichosis were enrolled. Genotyping using microsatellite markers linked to three autosomal recessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 10 publications
2
47
0
Order By: Relevance
“…The conditions used for amplification of the microsatellite markers were the same as described earlier (Azeem et al 2008).…”
Section: Extraction Of Genomic Dna and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions used for amplification of the microsatellite markers were the same as described earlier (Azeem et al 2008).…”
Section: Extraction Of Genomic Dna and Genotypingmentioning
confidence: 99%
“…The autosomal recessive forms of hair loss disorders have been shown to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupled receptor (P2RY5, MIM 609239) (Shimomura et al 2008;Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes. The genes for the three recently reported autosomal recessive forms of hair loss disorders (Naz et al 2010;Basit et al 2010a, b) have not been identified to date.…”
Section: Introductionmentioning
confidence: 98%
“…Likewise, the crystal structure of rhodopsin (7) suggests that the aspartic acid in TM2 makes a hydrogen bond with asparagine in TM1 and alanine in TM7; therefore, it too might contribute to the correct folding of GPCRs. Interestingly, single nucleotide polymorphisms of prolines in TM6 of rhodopsin (31) and the V2 vasopressin receptor (32,33) and aspartic acids in TM2 of the P2Y5/LPA6 receptor (34,35) and melanocortin 1 receptor (36) have been reported. Although precise analyses of these mutants have not been completed, these mutant receptors might be eliminated by the ER-associated degradation system because of their aberrant structures.…”
mentioning
confidence: 99%
“…This included congenital atrichia (MIM 203655) at 8p21 Nothen et al 1998), localized hereditary hypotrichosis (LAH, MIM 607903) at 18q12.1 (Kljuic et al 2003;Rafique et al 2003), autosomal recessive hereditary hypotrichosis (LAH2, MIM 609167) at 3q27.2 (Aslam et al 2004), LAH3 (MIM 611452) at 13q14.11-q21.32 (Wali et al 2007a) and hereditary hypotrichosis with skin vesicles (MIM 613102) at 18q21.1 ). All these five conditions congenital atrichia, LAH1, LAH2, LAH3 and hereditary hypotrichosis with skin vesicles have been reported to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003;Rafiq et al 2004), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupledreceptor (P2RY5, MIM 609239) (Pasternack et al 2008;Shimomura et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes, respectively. An autosomal dominant form of isolated hypotrichosis simplex of the scalp has been shown to result from mutations in corneodesmosin gene (CDSN, MIM 602593) (Levy-Nissenbau et al 2003).…”
Section: Introductionmentioning
confidence: 97%